Estimating the health impact of air pollution in Scotland, and the resulting benefits of reducing concentrations in city centres. (June 2019) - Lee, Duncan; Robertson, Chris; Ramsay, Colin; Gillespie, Colin; Napier, Gary
Highlights: We present a study of the health impact of exposure to air pollution in Scotland. We quantify the potential impact of reducing air pollution in city centres where Low Emission Zones (LEZ) are typically located. Air pollution affects respiratory disease but not cardiovascular disease. Reducing pollution in city centres will likely have a minimal impact on public health. Abstract: Air pollution continues to be a key health issue in Scotland, despite recent improvements in concentrations. The Scottish Government published the Cleaner Air For Scotland strategy in 2015, and will introduce Low Emission Zones (LEZs) in the four major cities (Aberdeen, Dundee, Edinburgh and Glasgow) by 2020. However, there is no epidemiological evidence quantifying the current health impact of air pollution in Scotland, which this paper addresses. Additionally, we estimate the health benefits of reducing concentrations in city centres where most LEZs are located. We focus on cardio-respiratory disease and total non-accidental mortality outcomes, linking them to concentrations of both particulate (PM10 and PM2.5 ) and gaseous (NO2 and NO x ) pollutants. Our two main findings are that: (i) all pollutants exhibit significant associations with respiratory disease but not cardiovascular disease; and (ii) reducing concentrations in city centres with low resident populations only provides a small health benefit.